Implementation of TEACCH in Learning for Students with Autism Spectrum Disorders in Special School - Anissa Sa’adah; Ahsan Romadlon Junaidi (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2021)
In education for children with autism spectrum disorders or ASD, appropriate learning methods are needed in order to develop their abilities and overcome difficulties due to their limitations. TEACCH (Treatment and Education of Autistic and Related Communication-handicapped Children) is one of the effective methods used in intervention for children with autism spectrum disorders. This study aims to describe the application of the TEACCH method in the learning of students with autism spectrum disorders at the primary education level in special schools. The research was conducted using a qualitative approach through case studies. Data was collected by observation, interviews, and documentation. Data analysis used the Miles & Huberman model. The research findings show that the process of implementing TEACCH in special schools goes through the stages of planning, implementation and evaluation. Planning includes: building a teacher's mindset, providing education to educators, forming an acceleration team (program coordinator, curriculum coordinator, and teachers), creating a support system and continuous evaluation. The implementation of TEACCH is shown from its structured teaching activities, namely: clear and coherent activities through a work system, clear and predictable activities through the use of activity schedules, structuring the physical structure of the learning environment, and the use of visual aids. Evaluation was conducted to assess the development of student learning outcomes and teacher performance in teaching.